Penerapan Metode Karyawisata dalam Pembelajaran Menulis Karya Sastra (Cerpen) - Dian Lufia Rahmawati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2013)
Literary learning in schools should be directed at developing students' appreciation of literature according to their level of emotional maturity. The development of literary learning creatively and innovatively tries to teach students to be willing and able to write literary works. The creative process of writers in creating literary works can be used as a reference in developing creative and innovative literary learning methods. One method used in the context of learning to write literature, especially short stories, is a method of field trip. The aim is so that students can observe directly and appreciate the phenomena around them, thus stimulating the emergence of ideas and creativity in learning to write short stories. The method of field trip that is carried out together in a pleasant atmosphere makes students able to develop character in socialization while gaining satisfaction in learning.